(untitled) (Revista Contexto & Saúde, 2024)
Objective: to identify the behavior, attitudes and practices of sex workers in relation to sexually transmitted infections (STIs). Methods: The Survey of Knowledge, Attitudes and Practices in the Brazilian Population was adapted and applied. Results: 182 sex workers participated, the age group from 18 to 30 years old was the most prevalent, natural and living in São Luís, brown, single and with dependents, with incomplete high school, use social name and work in nightclubs. They did not use a condom in the first sexual intercourse. Most know what STIs are and know the ways of transmission. A small number are aware of CTAs, PrEP and PEP. Conclusion: such knowledge makes it possible to plan actions and public policies for this population.